Effect of different East Coast Fever control strategies on disease incidence in traditionally managed Sanga cattle in Central Province of Zambia - Minjauw, B.; Otte, M.J.; James, A.D.; Castro, J.J. de; Sinyangwe, P. (Elsevier, 1998)
A clinical trial, comparing East Coast fever (ECF) control strategies in 5 different groups of traditionally managed Sanga cattle (44-49 animals per herd), was conducted in Zambia over 2.5 years between 1992 and 1995. Two groups were kept under intensive tick control by weekly cypermethrin (Barricade) treatment by hand spray (one group immunized by the infection-and-treatment method and one non-immunized), 2 groups were under no tick control (one immunized and one non-immunized), and a fifth, immunized group was maintained under strategic tick control (18 sprays/year). ECF-specific mortality was highest in the non-immunized and non-treated (control) group, while no difference in ECF-specific mortality could be observed between animals treated for ECF by immunization or by tick control. Acaricide treatment and/or immunization reduced the risk of clinical ECF by 92 percent . The highest incidence of ECF occurred in the adult Rhipicephalus appendiculatus season of 1993, just after immunization. The results of an artificial challenge experiment at the end of the field trial indicated that about 60 percent of the animals in the control group had become infected with Theileria parva without showing clinical signs. ECF incidence in non-vaccinated cattle declined 6 months after immunization, suggesting that the carrier state induced by immunization did not lead to a persistent high incidence, and might accelerate the progress to endemicity.